2020
DOI: 10.1071/an19051
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations and trends for traits of economic importance in dairy buffalo

Abstract: Context The planning and execution of selection programs requires estimates of the genetic correlations between traits. As genetic change is achieved for a given trait, it is important to consider possible genetic changes for other traits. Understanding the magnitude and direction of genetic correlations can assist in selection decisions. Aims The aim of the present study was to estimate the genetic correlations of reproductive traits with productive traits and with percentages of fat and protein in the milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some studies did not identify relationships between milk production and the reproductive performance of buffaloes [106][107][108][109]. Nevertheless, Vilela et al [110] reported a positive correlation between milk yield and age at first calving and the CI. These results, together with previous reports [19,54,103], highlight the importance of the proper design of genetic programs to improve milk yield in buffaloes to avoid negative consequences on reproductive efficiency, as previously suggested [67].…”
Section: Milk Yieldmentioning
confidence: 99%
“…Some studies did not identify relationships between milk production and the reproductive performance of buffaloes [106][107][108][109]. Nevertheless, Vilela et al [110] reported a positive correlation between milk yield and age at first calving and the CI. These results, together with previous reports [19,54,103], highlight the importance of the proper design of genetic programs to improve milk yield in buffaloes to avoid negative consequences on reproductive efficiency, as previously suggested [67].…”
Section: Milk Yieldmentioning
confidence: 99%